1995
DOI: 10.1136/bjsm.29.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Personal health benefits of Masters athletics competition.

Abstract: CanadaQuestionnaires (750 respondents, 44.4% response rate) examined the long-term health value of endurance exercise training in older age-classed competitors ('Masters Athletes', 551 men and 199 women) over a 7-year period (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992). The majority had initially completed maximal exercise tests. The weekly time devoted to training, competition and exercise-related travel was 10 to 30 h, and the annual expenditure on clothing, equipment and entrance fees was typically in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 13 publications
2
28
0
4
Order By: Relevance
“…Abstinence from cigarettes often precedes involvement in physical activity, both characteristics reflecting a health-conscious personality. 53 For a similar reason, many athletes consume large quantities of both water-soluble (C) and fat-soluble (E) vitamins, with potential benefit to the vascular system. The possible role of exercise as an appetite suppressant remains controversial.…”
Section: Lifestyle Changementioning
confidence: 99%
“…Abstinence from cigarettes often precedes involvement in physical activity, both characteristics reflecting a health-conscious personality. 53 For a similar reason, many athletes consume large quantities of both water-soluble (C) and fat-soluble (E) vitamins, with potential benefit to the vascular system. The possible role of exercise as an appetite suppressant remains controversial.…”
Section: Lifestyle Changementioning
confidence: 99%
“…In some instances, the incidence of infection has simply been compared with expectations for the general population. [33][34][35] In other studies, a comparison has been drawn with the experience of the same subjects prior to competition, 36,37 before augmenting physical training, 38,39 before augmenting the aerobic training mileage 32,40 or before an increase of fitness level. 41 In all reports where subjects have served as their own controls, findings are vulnerable to seasonal and secular trends in the incidence of infection.…”
Section: Epidemiological Methodologymentioning
confidence: 99%
“…The remaining four studies showed either no effect or a decrease in susceptibility to infection; none of these groups were particularly athletic. 41,[46][47][48] Of eight studies with intermediate ratings (8-13 points), five have noted an increased susceptibility to infection; four of these involved distance runners 32,36,40,43,49 and one a mixed sample of international competitors where 19 of 39 athletes had developed signs of chronic fatigue. 50 Of the three studies with a decrease in susceptibility to upper respiratory infection, one involved moderate exercise in elderly subjects 38 and two involved distance runners, 51 one being a group who were covering training distances of up to 42 km/week.…”
Section: Overall Quality Of Studies and Conclusionmentioning
confidence: 99%
“…Regarding masters sports, previous studies on the beneˆts of participation in masters sports have focused on health-related beneˆts, comparing the characteristics of masters athletes with the general population and reporting favorable results for masters athletes in terms of quality of life, lowered incidence of ischemic heart disease, hypertension, and diabetes (Shephard et al, 1995); better oral and dental health (Oba et al, 2004); signiˆcantly fewer incidents of physical and mental disease, high blood pressure, and arteriosclerosis, and less need for internal medicine, surgery, and dental consultations than the same age group in the general population (Bando et al, 2005;Bando et al, 2008); much higher physical performance levels than the average same-aged groups (Isaka, 2007); and moderate agerelated declines in physical performance (Young et al, 2008). In conclusion, previous studies on the beneˆts of sports and physical activities have been carried out using existing quantitative measurement scales.…”
Section: Previous Studies On the Beneˆts Of Sports And Physical Activmentioning
confidence: 99%